PERAN INFLUENCER MARKETING DAN TESTIMONI TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK DI E-COMMERCE SHOPEE PADA GENERASI Z DI KOTA DEPOK - Putri, Keysha Aeletta; Elyana, Instianti (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
This research investigates how influencer marketing and consumer testimonials on the purchase decisions of Generation Z in Depok City, focusing on cosmetic products sold on Shopee. The rapid growth of the digital cosmetic industry has made these marketing strategies crucial for engaging the largest and digitally active consumer group in Indonesia. Primary data were collected via Likert-scale questionnaires from 100 purposively sampled respondents between July and September 2025. Multiple linear regression analysis using SPSS showed that both influencer marketing (β positive, p < 0.05) and testimonials (β positive, p < 0.05) significantly influence consumer choices assessed secara terpisah maupun bersama-sama. Nilai determinasi  (R² = 0.784) indicates that 78.4% of the variation in purchase decisions is explained by these two variables. These findings highlight the importance for cosmetic marketers on Shopee to leverage influencer marketing and testimonials to effectively increase Generation Z's purchasing behavior.